Correlating CT findings of stroke with hyperglycemia in acute ischemic stroke patients - Shaker, Ameer (AL-Kindy College Medical Journal, 2019)
Background: Studies show that diabetic patients have a higher incidence of ischemic stroke than non-diabetic patients. In the Framingham study the incidence of thrombotic stroke was 25 times higher in diabetic men and 36 times higher in diabetic women than in those without diabetesObjectives: aim of this study to analyze topography in diabetic patients.Type of study:  Cross sectional study.Methods: 48 patients with acute stroke were classified into 4 groups: euglycemic, stress hyperglycemia, newly diagnosed diabetics, and known diabetics.Results:no significant differences were found in the type, site or size of stoke between the 4 groups, higher levels of blood sugars and hemoglobin HbA1cwere significantly higher with chronic white matter ischemia in stroke patients.Conclusions: hyperglycemia, diabetics and chronic glycemic disturbance may play role in the pathophysiology of white matter ischemia.